Can school health education improve students’ physical exercise time? Empirical research based on CEPS (2014–2015) survey data - Zhong, Huamei; Zhou, Jingjing; Xu, Dan; Liu, Tianbiao (Frontiers in Psychology, 2022)
Purpose School health education is an effective strategy for cultivating adolescent physical exercise habits by transmitting healthy knowledge; it helps to form healthy behaviours and encourages students to participate in physical exercise. The purpose of this study was to explore the relationship between school health education and student participation in physical exercise. Methods CEPS (China Education Penal Survey, 2014–2015) survey data were used to empirically analyse the impact of school health education on the time that students spend on physical exercise and the underlying mechanism of influence. Results The results showed that receiving a school health education increased the time that students spent on physical exercise. 1) Compared with receiving health education in only primary school or secondary school, receiving health education in both primary and secondary school had a greater impact on students spending time on physical exercise. 2) Receiving a school health education improved the time that students spend on physical exercise by improving students’ health perception and their sports interests. 3) Receiving a school health education had a more obvious impact on the physical exercise time of male students, nonrural resident students, and students from multi-child households. These findings can provide a reference for the seasonable settings of health education curriculum in schools.